Relationship between cytokines and β‐amyloid and Tau protein in the CSF of patients with Alzheimer's disease, amnestic mild cognitive impairment, and individuals without subjective cognitive impairment. (20th December 2022) - Burgos, Ivonne Carolina Bolaños; Hansen, Erika de Oliveira; Romano‐Silva, Marco Aurelo; Miranda, Debora; Viana, Bernardo de Mattos; Bicalho, Maria Aparecida Camargos; ,
Abstract: Background: The neuroinflammation process is one of the main pathological features of Alzheimer's disease (AD). In the course of AD, the deposits of β‐amyloid plaques and neurofibrillary tangles lead to over‐activation of the microglia, resulting in increased production of pro‐inflammatory and anti‐inflammatory cytokines that may contribute to neuronal dysfunction and cell death. Currently, several efforts have been made to discover the role of cytokines in AD's pathogenesis and the relationship between these inflammatory factors and the presence of AD's main biological markers (1). The present study aimed to determine the quantitative correlation between cytokines, β‐amyloid, and Tau proteins and the cognitive status of the participants. Method: CSF was collected by lumbar puncture from 80 older individuals with clinically defined AD (n=36), with amnestic mild cognitive impairment (aMCI) (n=24), and without objective cognitive impairment (n=20). CSF levels of β‐amyloid and p‐tau and t‐Tau and 27 cytokines were determined using the Luminex xMAP technique. Correlations were made between the cytokines, the β‐amyloid and Tau proteins levels, and the Mini‐Mental State test (MEEM). Result: considering all individuals, there was a significant positive correlation between Aβ42, IL‐4 and IL‐8; p‐Tau positively correlated with G‐CSF and GM‐CSF and finally p‐Tau/Aβ42 negatively correlated with IL8. The MEEM was correlated negatively with Eotaxin, IL‐6 and IL‐15. Focusing only in the AD group, there was a positive correlation for Aβ42 with IL‐4, IL‐8 and negatively with IL‐17; t‐Tau correlated negatively with IL‐1ra and IL‐5; p‐Tau/Aβ42 positively correlated with IL‐17 and negatively with IL‐8 and IP10. The MEEM showed a positive correlation with IL‐4. In the control group, Aβ42 and VEGF had a negative correlation; p‐Tau negatively correlated with TNF‐α; p‐Tau/Aβ42 were correlated positively with GM‐CSF, IL‐1β and IL‐6. The MEEM did not present any correlation. Between the aMCI group, t‐Tau was correlated positively with PDGF‐BB, and the MEEM was correlated negatively with Eotaxin. Conclusion: Changes in the neuroinflammatory profile are more prominent in AD patients compared to individuals without subjective cognitive impairment and those with aMCI.